Escherichia coli O157:H7 tir 255 T > A allele strains differ in chromosomal and plasmid composition - Weinroth, Margaret D.; Clawson, Michael L.; Harhay, Gregory P.; Eppinger, Mark; Harhay, Dayna M.; Smith, Timothy P. L.; Bono, James L. (Frontiers in Microbiology, 2023)
Shiga toxin-producing Escherichia coli (STEC) O157:H7 strains with the T allele in the translocated intimin receptor polymorphism tir 255 A > T gene associate with human disease more than strains with an A allele, however the allele is not thought to be the direct cause of this difference. We sequenced a diverse set of STEC O157:H7 strains (26% A allele, 74% T allele) to identify linked differences that might underlie disease association. The average chromosome and pO157 plasmid size and gene content was significantly greater within the tir 255 A allele strains.Eighteen coding sequences were unique to tir 255 A allele chromosomes and three were unique to tir 255 T allele chromosomes. There also were non-pO157 plasmids that were unique to each tir 255 allele variant. The overall average number of prophages did not differ between tir 255 allele strains, however, there were different types between the strains. Genomic and mobile element variation linked to the tir 255 polymorphism may account for the increased frequency of the T allele isolates in human disease.